A new approach for accurately measuring the spectral emissivity via modulating the surrounding radiation. (September 2022) - Zhang, Kaihua; Xu, Yanfen; Wu, Xiaohu; Yu, Kun; Liu, Yufang
Highlights: A new approach for accurately measuring the spectral emissivity was proposed. An emissivity measurement apparatus with high accuracy was constructed. The fluctuation of surrounding radiation is eliminated by the isothermal aperture. Abstract: Accurately measuring the spectral emissivity is of significant importance in thermal radiation. In this study, an improved measurement method for determination of spectral emissivity via modulating the surrounding radiation is proposed. A proof-of-concept measuring apparatus is constructed, and the main component parts are described in detail. The temperature uniformity of the isothermal aperture is verified, and the impact of the temperature uniformity on the emissivity measurements is studied. The good linearity and long-term stability of the detector is evaluated to ensure the validity of the improved method. The potential reference materials (silicon carbide and Armco iron) were used to validate the reliability and the accuracy of the measurement apparatus. The excellent data consistency of both two reference materials with the literature data demonstrates the reliability of the improved method and the measurement apparatus. The performance of the measurement apparatus with and without the isothermal aperture is compared, and the necessity of the modulated surrounding radiation is validated. The calculated combined uncertainty for the SiC sample at 1073 K is better than 2.38 %. The superior performance of the emissivity measurement apparatus indicate that the improved method proposed in this work provides a new approach for accurately measuring the spectral emissivity.